Dupilumab and tezepelumab in severe refractory asthma: new opportunities - Beatrice Ragnoli; Jaymin Morjaria; Patrizia Pignatti; Paolo Montuschi; Mariangela Barbieri; Lucrezia Mondini; Luca Ruggero; Liliana Trotta; Mario Malerba (SAGE Publishing, 2022)
Bronchial asthma is a chronic inflammatory condition with increasing prevalence worldwide that may present as heterogeneous phenotypes defined by the T2-mediated pattern of airway inflammation T2-high and T2-low asthma. Severe refractory asthma includes a subset of asthmatic patients who fail to control their disease despite maximal therapy and represent a group of patients needing marked resource utilization and hence may be eligible to add-on biological therapies. Among the new biologics, we focused our attention on two monoclonal antibodies: dupilumab, exerting a dual blockade of cytokine (interleukin (IL)-4 and IL-13) signaling; and tezepelumab, acting at a higher level preventing the binding of thymic stromal lymphopoietin (TSLP) to its receptor, thus blocking TSLP, IL-25, and IL-33 signaling, hence modulating airway T2 immune responses. With their different mechanisms of action, these two biologics represent important options to provide an enhanced personalized treatment regimen. Several clinical trials have been conducted testing the efficacy and safety of dupilumab in severe refractory asthmatic patients showing improvements in lung function, asthma control, and reducing exacerbations. Similar results were reported with tezepelumab that, differently from dupilumab, acts irrespectively on eosinophilic or non-eosinophilic phenotype. In this review, we provide an overview of the most important highlights regarding dupilumab and tezepelumab characteristics and mechanism of action with a critical review of the principal results of clinical (Phase II and III) studies concluded and those still in progress.